IMPLEMENTASI MEDIA “BARNETO” MELALUI METODE “DORA” UNTUK MENINGKATKAN KETERAMPILAN BERCERITA NARRATIVE BAHASA INGGRIS SISWA KELAS IX-E SMP NEGERI 4 TUBAN - Lilik Dyah Wulandari; Saliman Saliman (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
The activeness of inter-student English-language communication in class is still very lacking. Students tend to be passive and lack of confidence in communicating using English. Student’s ability in telling stories is still unsatisfactory. This research is intended to find alternative solutions to improve their abilities in narrative stories.